PROGRAM PENINGKATAN LITERASI KEUANGAN DAN LITERASI BISNIS DIGITAL BAGI CALON ENTERPRENEUR DI SMK LEBAK BARANG - Wahid Wachyu Adi Winarto; Novendi Arkham Mubtadi (LPPM Universitas Bina Bangsa, 2021)
A student is someone who studies in formal education, in this case, vocational students are expected to be able to gain expertise and skills as a provision to get and open a job. Students must be able to become entrepreneurs with new and innovative products. Vocational High School students can print entrepreneurial candidates after graduating from school so that they can help push the wheels of the national economy. Vocational students can be said to be prospective entrepreneurs, so they need to be equipped with digital business literacy and financial literacy in facing the development of the industrial revolution 4.0. This service activity is aimed at increasing the understanding of prospective entrepreneurs as well as improving skills in utilizing technology and the internet for business (business) in the digital era. The method used is workshop and training. The products produced are creative content from prospective entrepreneurs which can be in the form of vlog videos, promotional videos, and others. In addition, prospective entrepreneurs can also take advantage of the existing marketplace as a means of doing business (marketing). Community service activities have been carried out on Wednesday, April 14, 2021. Participants in the activity are class 12 students majoring in accounting from SMK Lebakbarang as many as 47 SMK students. The resource person for the activity was Wahid Wachyu Adi W, M.Si. (Lecturer) and Novendi Arkham M, M. Account. (Lecturer). The form of service activities is a workshop with material about digital business and financial literacy. Participants of service activities can follow well. The attendance rate is 83% until the activity ends. Participants also actively participated during the activity. Participants can carry out group assignments well, namely expressing ideas or business ideas in the digital era. The success of service activities is due to the service team being able to plan well and able to coordinate with collaboration partners intensively.